PENERAPAN PERMAINAN MATCH COLORS DALAM MENGEMBANGKAN MOTORIK HALUS ANAK USIA 3 TAHUN - Indri Ramahwanti; Deni Widjayatri (Fakultas Tarbiyah IIQ Jakarta, 2024)
The fine motor skills of 3 year old children need to be developed through play, because through play it will be easier for children to learn new information. The aim of this research is to develop the fine motor skills of 3 year old children in coordinating eye and hand movements through the application of the match colors game. The method used in this research is a qualitative method. Data collection techniques used are through observation and documentation. The subjects of this research were 3 year old children at Kindergarten Kartika Siliwangi 39 with a total of 6 children, 3 boys and 3 girls. The results of the research explain that on the critical thinking indicator there are 3 children with a fairly good assessment and there are 3 children with a good assessment. On the creative indicator, there are 2 children with quite good ratings and 4 children with good ratings. In the collaborative indicators, children's abilities were rated as quite good, obtained by 2 children and good assessments obtained by 4 children. So it can be concluded (1) the match colors game is able to develop the fine motoric aspects of 3 year old children well. (2) the match colors game can train hand and eye movement coordination. (3) the match colors game makes learning fun through playing.